Filling nanopipettes with apertures smaller than 50 nm: dynamic microdistillation - Salançon, Evelyne; Tinland, Bernard (Beilstein Journal of Nanotechnology, 2018)
Using nanopipettes with very small apertures (<10 nm) is a good way to improve the spatial resolution in scanning conductance experiments, to monitor single-molecule delivery and to strain long molecules stretching during translocation. However, such nanopipettes can be difficult to fill. Here we describe a dynamic microdistillation technique that successfully fills all nanopipettes, whatever their shape or tip radius. Even elongated or bent nanopipettes with a small-angle tip are completely filled using this new technique. The nanopipettes are first filled with pure water, which is later replaced with the desired electrolyte via electromigration. Electrical measurements are used to check that filling is complete.
Keywords: current rectification; distillation; filling; nanopipette